PUSARAN GLOBALISASI DAN RESIDU TRANSISI DEMOKRATISASI DI INDONESIA - Angga Nurdin Rahmat (Jurnal Academia Praja, 2018)
Unavioded Globalization for all countries and society has brought democracy that bring toward social and political condition. Democracy indeed can make a positif development for society, but in the new democratic countries, democracies seems make cause various social and political unrest in a society that is not yet fully capable to practiced democracy in full spektrum. Reffering from these conditions, this article will provide a discussion of how globalization has brought democracy and residue in Indonesia. This article uses qualitative methods with data obtained from literature review. This article is a report derived from a residue of democracy that is part of a communicator formed from conflict and disintegration of society. Therefore, the affirmation of the nation identity through Pancasila becomes the solution for the residue of democracy wich was difficult to avoid.